A Note on Discounted Cash Flow Examples: A Reply. - Goetz, Billy E. (The Accounting Review, 1973)
Presents a reply to a comments made on the article "A Problem in Discounted Cash Flow," published in an earlier issue of the journal "The Accounting Review." Problem of the precision required in the tables one uses to expedite his calculations; Improbability of the instances predicting losses in some periods, to secure the alternating signs that signal the possibility of multiple interest rates; Statement that using one year as a period length is arbitrary.